Designing a Multimedia-Based Tourism Information System for Tetebatu Village Using the Design Thinking Approach - Arfin, Ahmad; Saputra, Wahyu; Firmansyah, Firmansyah (Universitas Islam Al-Azhar Mataram, 2024)
One of the communities in the East Lombok area that has a lot of tourism potential is Tetebatu Village. Unfortunately, lack of awareness and promotion has hindered the full realization of this potential. A tourism information system application is needed that can provide accurate and comprehensive information and marketing to tourists to overcome these problems. The user interface and user experience of the Jepara Regency tourism information system application were created using the design thinking process in this research. This approach was chosen because it allows users to be involved in the design process, resulting in a product tailored to the user's needs and preferences. Research findings show that the Tetebatu Village tourism information system application was created with an intuitive and adaptable user interface. Apart from that, this application has a number of features that can facilitate tourists' access to information and promotions related to tourism in Tetebatu Village.